2017
DOI: 10.3390/e19050227
|View full text |Cite
|
Sign up to set email alerts
|

Ion Hopping and Constrained Li Diffusion Pathways in the Superionic State of Antifluorite Li2O

Abstract: Li 2 O belongs to the family of antifluorites that show superionic behavior at high temperatures. While some of the superionic characteristics of Li 2 O are well-known, the mechanistic details of ionic conduction processes are somewhat nebulous. In this work, we first establish an onset of superionic conduction that is emblematic of a gradual disordering process among the Li ions at a characteristic temperature T α (~1000 K) using reported neutron diffraction data and atomistic simulations. In the superionic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Recent work has further confirmed this collective exchange motion in Li salt materials is in connection to solidstate batteries. 31,105 Eapen and coworkers [25][26][27] have also examined this kind of collective motion recently for a range of type II superionic materials (CaF2, UO2, LiO2) where it was suggested that ionic conductivity in these materials is governed by the lifetime of the string like ion clusters defined by a time at which the number of particles in string clusters become maximized. While this work unequivocally establishes the existence of string-like excitations in these materials and provided much needed quantification of the average properties, the agreement of the model predictions with simulation data is only qualitative.…”
Section: Collective Atomic Motion In Condensed Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has further confirmed this collective exchange motion in Li salt materials is in connection to solidstate batteries. 31,105 Eapen and coworkers [25][26][27] have also examined this kind of collective motion recently for a range of type II superionic materials (CaF2, UO2, LiO2) where it was suggested that ionic conductivity in these materials is governed by the lifetime of the string like ion clusters defined by a time at which the number of particles in string clusters become maximized. While this work unequivocally establishes the existence of string-like excitations in these materials and provided much needed quantification of the average properties, the agreement of the model predictions with simulation data is only qualitative.…”
Section: Collective Atomic Motion In Condensed Materialsmentioning
confidence: 99%
“…24 Simulations of a wide range of glass-forming materials under equilibrium conditions, both polymer and metallic glass materials, have further indicated that the change in the activation free energy governing diffusion and relaxation can be quantified by the change in the average cooperative exchange events ('strings') and it is currently a question whether these structures might have the same significance for heated crystals. Annamareddy and Eapen [25][26][27] have recently made studies of string-like collective motion in simulations of UO2, LiO2 and fluorite materials, where superionic dynamics has long been observed with a view of obtaining a corresponding quantitative description of transport in terms of string dynamics. While these simulation results are highly suggestive, they do not support a coherent picture of relaxation and diffusion that was found before in cooled liquids.…”
Section: Introductionmentioning
confidence: 99%
“…49 It is also worth mentioning that, other conductivity mechanisms were proposed where H 3 O + or OH − ions could be responsible for conductivity while dissociated ions of the salt and water are passive and work as a substrate. 50 Another conductivity mechanism is the string-like ionic movement where ions hop between lattice sites 51 while diffusion is constrained. For example, lithium ion hopping between tetrahedral sites in antifluorite Li 2 O, or other superionic conductors enter a jamming state that can resemble structures that cause the C max .…”
Section: More On the Structure Of Licl/h 2 O Solutionsmentioning
confidence: 99%
“…Numerous molecular dynamics studies of Li 2 O have also been performed. [27][28][29][30][31][32][33][34][35] The simulations indicate that hopping of vacancies between lithium sites dominates the conduction behavior up to about 930°C. 29 Above this temperature, various transport pathways have been suggested involving vacancies, 33,34 interstitials, [29][30][31] or cooperative motion.…”
mentioning
confidence: 93%
“…29 Above this temperature, various transport pathways have been suggested involving vacancies, 33,34 interstitials, [29][30][31] or cooperative motion. 28 Defect clusters have also been simulated, and various association energies were obtained. 36 Isotope exchange measurements confirmed that the diffusivity of O 2− is about five orders of magnitude lower than that of Li + , despite a modest enhancement of the former at grain boundaries.…”
mentioning
confidence: 99%